Psychometrics and Validation of the Intensive Care Unit Memory Assessment Tool in the Iranian Population - Sara Ghafouri; Simin Jahani; Elham Maraghi; Somayeh Biparva Haghighi; Neda Sayadi (Caspian Journal of Neurological Sciences, 2023)
Background: The intensive care unit memory (ICUM) assessment tool is a practical tool for memory monitoring after the discharge from ICU. Objectives: This psychometric study purported to validate ICUM for a sample population of Iranian patients hospitalized in ICU. Materials & Methods: This research was a descriptive-analytical study that was conducted at Ahvaz University of Medical Sciences in 2022. A total of 96 patients were selected through the convenience sampling method and were asked to complete the questionnaire 2 weeks and 8 weeks after their discharge from the hospital. Exploratory factor analysis was run to validate the tool’s structure. The reliability of the ICUM tool was checked by the testretest method and the Cronbach alpha coefficient for memory subscales. Results: To increase the qualitative face and content validity of the tool in Persian, some vague items were modified according to the suggestions of the participants, language, and nursing experts. For the quantitative face validity, the item coefficient was calculated, and the minimum score obtained was 4.4. For the quantitative content validity, the content validity ratio (CVR) and content validity index (CVI) were calculated. The minimum obtained scores were CVI=0.7 and CVR=0.6. Thus, all the items were confirmed. The implementation of the factor analysis was confirmed with KMO=0.65. The highest Cronbach alpha coefficient for delusional memory was 0.62 and the highest test-retest correlation for factual memory was 0.95. Conclusion: The Persian version of ICUM has strong test-retest reliability, but weak internal consistency reliability. It is recommended that future studies evaluate the tool’s reliability over an extended period.